Peningkatan Partisipasi dan Prestasi Belajar Siswa melalui Implementasi Cooperative Learning Strategy Tipe Numbered Head Together (NHT) - siti juwariyah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2017)
Abstract This study aims to determine the implementation of cooperative learning strategy NHT can increase participation and student achievement in the material survival of living beings subjects of Natural Sciences (IPA) in the class IX-B MTsN Gondowulung. This research is a class act. The study was conducted in three cycles. Each cycle consisted of three meetings. The results showed that the implementation of cooperative learning strategy NHT can increase participation and student achievement in the material survival of living beings subjects of Natural Sciences (IPA) in the class IX-B MTsN Gondowulung. Increasing the participation of student learning based on data from the questionnaire are: 62.58% in early learning, 69.43% in cycle I, 70.65% in cycle II, and 72.79% in cycle III. The entire cycle in the high category. Improving student achievement can be seen from the number of students who completed the classical completeness. The number of students increased from 4 students completed the placement test is 16 students in cycle I, 13 students in cycle II, and 19 students in cycle 3. Classical completeness increased from 13.33% at the placement test became 53.33% in cycle I, 43.33% in cycle II, and 63.33% in cycle III. Keywords: Student Participation, Student Achievement, Implementation of Cooperative Learning Strategy type NHT Abstrak Penelitian ini bertujuan untuk mengetahui implementasi cooperative learning strategy tipe NHT dapat meningkatkan partisipasi dan prestasi belajar siswa pada materi kelangsungan makhluk hidup mata pelajaran Ilmu Pengetahuan Alam (IPA) di kelas IX-B MTsN Gondowulung. Penelitian ini merupakan penelitian tindakan kelas. Penelitian dilakukan dalam 3 siklus. Setiap siklus terdiri dari 3 pertemuan. Hasil penelitian menunjukkan bahwa implementasi cooperative learning strategy tipe NHT dapat meningkatkan partisipasi dan prestasi belajar siswa pada materi kelangsungan hidup makhluk hidup mata pelajaran IPA di kelas IX-B MTsN Gondowulung. Peningkatan partisipasi belajar siswa berdasarkan data hasil angket yaitu: 62,58% pada awal belajar, 69,43% pada siklus I, 70,65% pada siklus II dan 72,79% pada siklus III, seluruh siklus dalam kategori tinggi. Peningkatan prestasi belajar siswa dapat dilihat dari jumlah siswa yang tuntas dengan ketuntasan klasikal. Jumlah siswa tuntas meningkat dari 4 siswa pada tes penempatan yaitu 16 siswa pada siklus I, 13 siswa pada siklus II, dan 19 siswa pada siklus III. Ketuntasan klasikal mengalami peningkatan dari 13,33% pada tes penempatan menjadi 53,33% pada siklus I, 43,33% pada siklus II, dan 63,33% pada siklus III. Kata Kunci: Partisipasi Belajar Siswa, Prestasi Belajar Siswa, Implementasi Cooperative Learning Strategy Tipe Numbered Head Together (NHT)